Pharmacological effects and target analysis of Guipi wan in the treatment of cerebral ischemia-reperfusion injury - Zhang, Jianfeng; Luo, Li; Guo, Yanyan; Liu, An; Zhang, Mengjia; Jiang, Wei; Li, Xi; Liu, Qingqing; Yu, Jiaoyan (Frontiers in Pharmacology, 2024)
Guipi wan (GPW) is a traditional Chinese medicine commonly used in clinical practice, typically to treat neurological diseases such as neurasthenia and traumatic brain injury. It may have positive effects on cerebral ischemia‒reperfusion injury (cI/R). This study aimed to assess the effects of GPW in a mouse model of cI/R and find its possible targets. C57BL/6J mice were used to establish the cI/R model, and the laser speckle doppler was used to determine the success of the model. GPW was administered intragastrically for 7 days, brain tissue sections were stained with TTC, HE, and TUNEL, Western blot assay was performed to detect the effect of apoptosis-related proteins. Furthermore, we screened active ingredients from the TCM Database and constructed a compound‒target network using the Cytoscape 3.8.0 software. Moreover, we employed protein‒protein interaction and component‒target‒pathway network analyses to determine the potential components of GPW and its target genes, the key target was verified through molecular docking. Finally, we detected the influence of the downstream signaling pathway of the target through Western blot. The results showed that GPW decreased the cerebral infarction area, neurological function scores, and neuronal apoptosis in mice by regulating PI3K/AKT signaling pathway. Network analysis indicated that gamma-aminobutyric acid B receptor 1 (GABBR1) might be a potential target for the treatment of cI/R. Molecular docking indicated that 9 active components in GPW could bind to GABBR1 with desirable binding energy. This study represented the demonstratable effect of GPW in the treatment of cI/R injury and suggested GABBR1 as a potential target using network analysis.